PERBEDAAN HASIL BELAJAR SOSIOLOGI MENGGUNAKAN METODE CERAMAH DENGAN DEEP LEARNING APPROACH KELAS XI IPS SMAN 2 PAINAN, SKRIPSI, PROGRAM STUDI PENDIDIKAN SOSIOLOGI STKIP PGRI SUMATERA BARAT, PADANG, 2014. - Yulia, Yovita - (Pendidikan Sosiologi, 2014)
The main problem of the research was: Is there a difference level ofSociology Achievement taught by using Deep Learning Approach and LectureMethod. The purpose of this research was to analyze a difference level ofSociology Achievement taught by using Deep Learning Approach and LectureMethod.Theory has been used was Constructivism. The purpose of this theory wasto describe how a Science and Knowledge gained. This research used quantitativeapproach. The design of this research was and Experimental research. The sampleof this research consists of 60 Students, divided into two classes. These twoclasses were decided to be experimental class (XI IPS 1) with amount of 31Students and control class (XI IPS 3) consists of 29 students. The instrument ofthis research was a written test, it consisted 20 multiple choice questions that havebeen tested. The data were analyzed by using T- test formula.The result of this research shown that the mean score of experimental classwas 73,23, median 75, and mode 75 with 10,372 standard of deviation while thecontrol class had mean score 64,3, median 65 and mode with 15,63 standard ofdeviation. From the calculation of the T- test, it was indicated that t calculatedwas 2,586 and t table = 1,67065 at the significant level was 5%. It mean tcalculated greater than t table (t calculated > t table) so in the other word Hahypothesis accepted and null hypothesis was rejected. From these results it can beconcluded that there are significant differences in the average results ofsociological learning achievement using deep learning approach and a lecturemethod. Based on the calculation results obtained average difference levellearning achievement between students who are taught with methods of deeplearning approach and students taught by lecture method is equal to 8.93.